CMOS Silicon-on-Sapphire RF Tunable Matching Networks - Chamseddine Ahmad; Haslett James W; Okoniewski Michal (EURASIP Journal on Wireless Communications and Networking, 2006)
This paper describes the design and optimization of an RF tunable network capable of matching highly mismatched loads to 50 at 1.9 GHz. Tuning was achieved using switched capacitors with low-loss, single-transistor switches. Simulations show that the performance of the matching network depends strongly on the switch performances and on the inductor losses. A 0.5 m silicon-on-sapphire (SOS) CMOS technology was chosen for network implementation because of the relatively high-quality monolithic inductors achievable in the process. The matching network provides very good matching for inductive loads, and acceptable matching for highly capacitive loads. A 1 dB compression point greater than dBm was obtained for a wide range of load impedances.